The Effect Of Jigsaw Teaching Technique To The Reading Comprehension Of Grade Eight Students Of Smp Negeri 2 Tapian Dolok On A Descriptive Text - Rika Sinaga; Sanggam Siahaan; Partohap Saut Raja Sihombing (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The aim of this research is to describe and analyze reading comprehension teaching techniques using jigsaw teaching techniques for eighth grade students at SMP Negeri 2 Tapian Dolok. The aim of this research is to determine the effect. Jigsaw Teaching Technique on reading comprehension of eighth grade students of SMP Negeri 2 Tapian Dolok on descriptive text. This research uses a quantitative type of research with a quasi-experimental design. The sampling technique used in this research was purposive sampling, with a sample of 62 class VIII students at SMP Negeri 2 Tapian Dolok. Two classes were taken as subjects for this research, namely the experimental class and the control class. Data obtained from the experimental class and control class were analyzed using the t-test formula. Researchers found that the post-test average in the experimental group was 83 and the post-test average in the control group was 77. The calculation results showed that at the 5% significance level, the t-count value > t-table (2.4 > 1.671 ). From these results, it appears that there is a significant difference between student achievement in reading comprehension of descriptive texts that use jigsaw teaching techniques and those taught using traditional lecture-based teaching methods. Therefore, the researchers concluded that there was a significant influence of the Jigsaw teaching technique on reading comprehension.